Antimicrobial Resistance in Staphylococci Isolated From Various Clinical Specimens of Inpatients in Intensive Care Units: A 4-year Evaluation - Zerife Orhan; Arzu Kayış; Burak Küçük; Adem Doğaner; Murat Aral (Türk Yoğun Bakim Derneği Dergisi, 2024)

(untitled)
Objective: The aim of this study was to evaluate the change in methicillin resistance and antibiotic susceptibility of staphylococcal strains isolated from various clinical samples of patients hospitalized in intensive care units over the years. Materials and Methods: A total of 5144 staphylococcal strains isolated from various clinical specimens of inpatients in intensive care units in a university health practice and research hospital medical microbiology laboratory between January 2018 and December 2021 were (96.51%) included in the study. Bacteria identification and antibiotic susceptibility tests were performed using conventional methods and an automated systems. Results: Of the total 5144 staphylococci strains, 4503 were identified as coagulase-negative staphylococci (CNS) (87.54%) and 641 as Staphylococcus aureus (S. aureus) (12.46%). Of these strains, 1451 (28.21%) were isolated from anesthesiology and reanimation intensive care unit, and 4573 (88.90%) from blood samples. The most dramatic increase in both S. aureus and CNS in 2021 occurred in levofloxacin (S. aureus 100%; CNS 99.45%) and ciprofloxacin (S. aureus 100%; CNS 98.54%). While a high rate of resistance to fusidic acid (96.51%) was observed in CNSs, the resistance, which was over 65% in S. aureus strains, decreased significantly (5.40%) in 2021. The lowest antibiotic resistance was in daptomycin, linezolid, and teicoplanin in both bacterial groups. Methicillin resistance, which was 62.31% in 2018 in S. aureus strains, decreased to 33.10% in 2021, while it decreased from 86.68% to 75.06% in CNSs. The rate of resistance to all the examined antibiotics were found to be significantly higher in CNSs. Conclusion: To prevent the development of resistance, antimicrobial resistance profiles should be determined through effective surveillance studies, and each hospital should establish its own antibiotic use policy. Additionally, it is important to ensure the rational use of antibiotics and to take effective infection control measures.